Komputasi energi elektronik pembentukan kitosan dari kitin cangkang udang dan pengaruhnya akibat keberadaan logam berat - Bayu Fernanda (Department of Physics – Universitas Negeri Padang UNP, 2016)
Shrimp waste in the form of skin, head and tail of a substance containing protein and chitin can be processed into chitosan which has many uses. Chitosan is obtained from chitin which is reacted with NaOH. Chitosan can be processed and used as an absorbent material heavy metals generated by industrial waste. Owned energy chitosan obtained by Ev 798,4. However kitosani formation process, and how the influence of the presence of heavy metals to the energy can not be explained. Based on that, the purpose of this study was to determine the change in potential energy and activation energy in the formation of chitosan and the influence of the presence of heavy metals to energy chitosan.This research was a theoretical study that uses CS software Chemoffice and winmopac to see the chitosan molecular electronics and pengruh heavy metals. Using this software obtained data such as the distance between molecules, molecular charge and potential energy at the time of formation of chitin chitosan reacted with NaOH. Then chitosan is reacted with heavy metals, from here will be visible effect of heavy metals on the energy chitosan